Pengaruh Word Of Mouth, Brand Awareness, Brand Image, Brand Trust, Dan Harga Terhadap Keputusan Pembelian Rokok Gajah Baru (Studi Pada Konsumen Rokok Gajah Baru Di Kec. Pagak) - Kholidah, Amalya Nur Maya; Arifin, Rois; Mustapita, Arini Fitria (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This studi aims to determine how much influence word of mouth, brand awareness, brand image, brand trust, and price have on purchasing decisions for Gajah Baru Cigarettes (study of consumers of Gajah Baru Cigarettes in Pagak District). The number of samples was determined using the Maholtra formula and the results obtained were 72 respondents. Data was obtained by distributing questionnaires to consumers of Gajah Baru Cigarettes and selected using snowball sampling. Data analysis in this study used SPSS. Data testing techniques used in this research include validity test, reliability test, normality test, classical assumption test, multiple linear regression analysis test, f test, t test and coefficient of determination test (adjusted R2). The results of this research show that word of mouth and price have a positive and significant effect on purchasing decisions. Meanwhile, brand awareness, brand image and brand trust have no influence on purchasing decisions.Keywords: Word of Mouth, Brand Awareness, Brand Image, Brand Trust, Price, and Purchasing Decisions